PENDAYAGUNAAN STRUKTUR TEKS WACANA KESEJAHTERAAN RAKYAT DALAM TAJUK RENCANA HARIAN KOMPAS - Wulandari, Yosi (Universitas Muhammadiyah Surakarta, 2012)
ABSTRACTLanguage usage shows that language has important role and power in changingevents. Kompasâa national daily newspaperâhas a unique language characteristic, particularly the one used in editorial. Research on critical discourse analysis of empowering text structure in editorial is crucial to be conducted. The purpose of this research is to explain the empowerment of thematic, schematic, syntactic, and stylisticstructure of discourse in Kompas editorial. This is qualitative research of which object is editorial of Kompas and the data is the text structure of educational, health and environment, and social discourse. The data is collected by documentation technique and it is analyzed by content analysis. The findings show that (Keywords: empowering text structure, public welfare discourse, Kompas editorial